Silane-terminated polyaspartic acid ester as well as preparation method and application thereof

By preparing silane-terminated polyaspartic acid ester, a highly weather-resistant base-to-base anti-corrosion coating was prepared, which solved the problems of low corrosion resistance, short service life and poor substrate adhesion of existing coatings, and achieved excellent substrate adhesion and wear resistance.

CN120682460APending Publication Date: 2025-09-23SHANXI ARCHITECTURE KEXUE RES YUAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510852877.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing anti-corrosion coatings have problems such as low corrosion resistance, short service life, and poor adhesion to substrates, which limit their application and development.

Method used

Silane-terminated polyaspartic acid ester is used as the key raw material to prepare a highly weather-resistant base-to-base anti-corrosion coating. Through the cross-linking reaction of silane-terminated polyaspartic acid ester and polyisocyanate, a coating with excellent substrate adhesion and wear resistance is formed.

Benefits of technology

The coating achieves excellent substrate adhesion, wear resistance and weather resistance, solves the problems of low corrosion resistance and short service life of existing coatings, and does not require primer for use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120682460A_ABST
    Figure CN120682460A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of anticorrosive paint, in particular to silane-terminated polyaspartic acid ester as well as a preparation method and application thereof. The silane-terminated polyaspartic acid ester has a structure represented by a general formula (1), wherein R is a C2-C15 divalent aliphatic group. The silane-terminated polyaspartic acid ester disclosed by the invention is mild in preparation process condition and high in silane terminating rate, and can be used as a raw material for preparing a high-weather-resistance primer-topcoat anticorrosive coating. When a base material is coated with the high-weather-resistant primer-topcoat anticorrosive paint, a coating film formed by the paint has excellent corrosion resistance (such as acid resistance, salt water resistance and salt fog resistance), artificial aging resistance, wear resistance and base material adhesion. General formula (1)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-corrosion coatings, and in particular to silane-terminated polyaspartic acid ester and a preparation method and application thereof. Background Art

[0002] Anti-corrosion coatings are widely used in construction, railways, bridges, petroleum, chemical industry, metallurgy and other fields. Every year, about 30% of steel is scrapped due to corrosion. The development of high-quality anti-corrosion coatings has become an urgent task in the current research and development of new materials technology. Currently, anti-corrosion coatings are limited by the chemical properties of traditional resins and face application problems such as low corrosion resistance, short service life, and poor substrate adhesion. These have greatly restricted the application and development of anti-corrosion coatings. Therefore, the development of anti-corrosion coatings with excellent corrosion resistance, long service life, and high substrate adhesion is an urgent problem to be solved in the field of anti-corrosion coatings.

[0003] Polyaspartic acid ester polyurea is an aliphatic, slow-reacting polyurea material with excellent mechanical properties, aging resistance, and corrosion resistance. It is widely used in high-strength elastomers, corrosion and wear protection, building protection, and explosion protection. As a key raw material for the synthesis of polyaspartic acid ester polyurea, polyaspartic acid ester (PAE) is a sterically hindered aliphatic secondary diamine. Due to the synergistic effects of the electron induction effect of adjacent groups and the steric shielding effect of the coronal structure, the amino group activity is reduced, which prolongs the gel time with polyisocyanates, thereby improving the mechanical properties of polyaspartic acid ester polyurea. Furthermore, since PAE's molecular structure does not contain color-discoloring groups, polyaspartic acid ester polyurea prepared from PAE exhibits excellent yellowing and aging resistance. However, due to its internal structure, the polyurea material lacks strong chemical bonding with some substrates and can only rely on physical adsorption and mechanical bite to adhere to the substrate. As a result, the polyurea coating needs to be used in conjunction with a primer, affecting construction efficiency and restricting the development of polyaspartic acid polyurea in the coatings field.

[0004] Therefore, the current general demand in this field is to develop a new polyurea anti-corrosion coating with excellent substrate adhesion, mechanical properties and anti-corrosion properties (such as acid resistance, salt water resistance, salt spray resistance, artificial aging resistance, etc.), while having good workability. Summary of the Invention

[0005] Based on the above-mentioned problems, the purpose of the present invention is to provide a silane-terminated polyaspartic acid ester and a preparation method thereof, and a highly weather-resistant bottom-to-top anti-corrosion coating containing the silane-terminated polyaspartic acid ester to address the deficiencies in the prior art. To address the above-mentioned problems, the present invention first provides a silane-terminated polyaspartic acid ester, which has a simple process and low production cost. In addition, the highly weather-resistant bottom-to-top anti-corrosion coating prepared using the synthesized silane-terminated polyaspartic acid ester as a key raw material has good weather resistance, wear resistance, and excellent substrate adhesion, solving the current application problems of anti-corrosion coatings such as low corrosion resistance, short service life, and poor substrate adhesion.

[0006] To achieve the above object, the technical solution of the present invention is as follows: A silane-terminated polyaspartic acid ester having a structure represented by the following general formula (1):

[0007] General formula (1) Where R is C2-C 15 A divalent aliphatic group.

[0008] The preparation method of the silane-terminated polyaspartic acid ester as described above comprises the following steps: (1) slowly adding maleate to aliphatic diamine under nitrogen protection, stirring and heating to react, thereby obtaining polyaspartic acid ester; (2) adding 3-aminopropyltriethoxysilane and a catalyst to the polyaspartic acid ester obtained in step (1), mixing and heating while performing reduced pressure distillation to remove the generated by-products, thereby obtaining the silane-terminated polyaspartic acid ester.

[0009] According to certain preferred embodiments of the present invention, the aliphatic diamine is selected from one or more of ethylenediamine, 1,4-butanediamine, 1,6-hexanediamine, 1,4-cyclohexanediamine, 1,8-octanediamine, 1,10-decanediamine, isophoronediamine, 4,4'-diaminodicyclohexylmethane, and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane.

[0010] According to certain preferred embodiments of the present invention, the maleate is selected from one or more of dimethyl maleate, diethyl maleate, and dibutyl maleate.

[0011] According to certain preferred embodiments of the present invention, the catalyst is selected from one or more of pyrrole compounds, pyridine compounds, imidazole compounds, and pyrimidine compounds.

[0012] According to certain preferred embodiments of the present invention, the catalyst is selected from one or more of 2,3-dihydroxypyridine, 4,6-dimethylpyrimidine, 4-hydroxymethylpyrimidine, 3-hydroxy-6-methylpyridine, 4-benzylpyridine, 5-methylpyrimidine, 2,4-dimethoxypyrimidine, 2,4,6-trimethoxypyrimidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 1,5-diazabicyclo[4.3.0]-5-nonene.

[0013] According to certain preferred embodiments of the present invention, the molar ratio of the aliphatic diamine to the maleate is 1:2.

[0014] According to certain preferred embodiments of the present invention, the molar ratio of the 3-aminopropyltriethoxysilane to the polyaspartic acid ester is 4:1 to 4.2:1.

[0015] According to certain preferred embodiments of the present invention, the ratio of the weight of the catalyst to the sum of the weights of the polyaspartic acid ester and 3-aminopropyltriethoxysilane is 5×10 -4 : 1 to 1×10 -3 : 1.

[0016] The silane-terminated polyaspartic acid ester described above is used to prepare a highly weather-resistant bottom-to-top anti-corrosion coating.

[0017] A highly weather-resistant bottom-to-top anti-corrosion coating, comprising component A and component B, wherein: Component A: 50-80 parts by weight of the silane-terminated polyaspartic acid ester described above, 10-30 parts by weight of rutile titanium dioxide, 0.5-1.5 parts by weight of a dispersant, 0.5-0.8 parts by weight of a defoamer, 0.1-0.3 parts by weight of a leveling agent, 1-4 parts by weight of a chemical dewatering agent, 0.3-0.6 parts by weight of a UV absorber, and 2-20 parts by weight of a solvent; Component B: 10-15 parts by weight of HDI trimer, 50-75 parts by weight of polyisocyanate elastic curing agent, and 10-20 parts by weight of solvent; The component A and the component B are packaged in an isolated manner to obtain the highly weather-resistant bottom-and-top integrated anti-corrosion coating.

[0018] According to certain preferred embodiments of the present invention, in the above-mentioned highly weather-resistant bottom-to-top anti-corrosion coating: The dispersant is an anionic wetting and dispersing agent; and / or The defoamer is a polyolefin solution type defoamer; and / or The leveling agent is one or more of an organosilicon leveling agent and a modified acrylic leveling agent; and / or The chemical dewatering agent is a vinylsilane chemical dewatering agent; and / or The ultraviolet absorber is one or more of a benzophenone ultraviolet absorber, a salicylate ultraviolet absorber, a benzotriazole ultraviolet absorber, a substituted acrylonitrile ultraviolet absorber and a triazine ultraviolet absorber; and / or The solvent is selected from one or more of butyl acetate, diethyl carbonate, propylene glycol methyl ether acetate and xylene.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1) The silane-terminated polyaspartic acid ester synthesized according to the present invention has a high silane-terminated rate; 2) The process for synthesizing silane-terminated polyaspartic acid ester according to the present invention is simple and the reaction conditions are mild; 3) The anti-corrosion coating prepared according to the present invention has a high cross-linking density and excellent wear resistance and substrate adhesion; 4) The anti-corrosion coating prepared according to the present invention has excellent weather resistance and yellowing resistance. DETAILED DESCRIPTION

[0020] The present invention will be described in further detail below in conjunction with specific embodiments. It will be understood that other embodiments are contemplated and may be implemented without departing from the scope or spirit of the present invention. Therefore, the following detailed description is non-restrictive.

[0021] Unless otherwise indicated, all numbers used in the present specification and claims to indicate feature sizes, quantities, and physicochemical properties should be understood as being modified in all cases by the term "about". Therefore, unless otherwise indicated, the numerical parameters listed in the above description and the appended claims are approximate values, and those skilled in the art will be able to appropriately change these approximate values ​​by utilizing the teachings disclosed herein to seek to obtain the desired properties. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0022] As mentioned above, there is an urgent need in the prior art to develop a silane-terminated polyaspartic acid ester and a preparation method thereof, as well as a highly weather-resistant bottom-to-top anti-corrosion coating comprising the silane-terminated polyaspartic acid ester.

[0023] Through intensive research, the inventors of the application have developed a novel silane-terminated polyaspartic acid ester to address the shortcomings of the prior art. The silane-terminated polyaspartic acid ester according to the present invention has low production costs, simple processes, and mild reaction conditions. In particular, the silane-terminated polyaspartic acid ester can be used as a resin in the preparation of anti-corrosion coatings. The resulting anti-corrosion coatings exhibit excellent substrate adhesion, eliminating the need for primers. Furthermore, the cured anti-corrosion coatings exhibit excellent wear resistance and weather resistance.

[0024] According to one aspect of the present invention, there is provided a silane-terminated polyaspartic acid ester having a structure represented by the following general formula (1):

[0025] General formula (1) Where R is C2-C 15 A divalent aliphatic group.

[0026] According to another aspect of the present invention, there is provided a method for preparing silane-terminated polyaspartic acid ester, the method comprising the following steps: (1) slowly adding maleate to aliphatic diamine under nitrogen protection, stirring and heating to react, thereby obtaining polyaspartic acid ester; (2) adding 3-aminopropyltriethoxysilane and a catalyst to the polyaspartic acid ester obtained in step (1), mixing and heating while performing reduced pressure distillation to remove the generated by-products, thereby obtaining the silane-terminated polyaspartic acid ester.

[0027] The inventors of the present invention have discovered that the aliphatic group R present in the structure of the silane-terminated polyaspartic acid ester prepared according to the above method not only affects the gel time of the silane-terminated polyaspartic acid ester but also has a significant impact on the physical properties of the coating product containing the silane-terminated polyaspartic acid ester after curing. More preferably, when the aliphatic diamine is selected from one or more of 4,4'-diaminodicyclohexylmethane and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, the physical properties of the synthesized silane-terminated polyaspartic acid ester are optimal.

[0028] Preferably, the maleate is selected from one or more of dimethyl maleate, diethyl maleate, and dibutyl maleate.

[0029] According to certain preferred embodiments of the present invention, a strongly basic organic nitrogen heterocyclic catalyst is used to catalyze the aminolysis reaction between the ester groups at the ends of polyaspartic acid ester and the primary amine groups in 3-aminopropyltriethoxysilane. Preferably, the strongly basic organic nitrogen heterocyclic catalyst is one or more of a pyrrole compound, a pyridine compound, an imidazole compound, and a pyrimidine compound.

[0030] More preferably, the catalyst is one or more of 2,3-dihydroxypyridine, 4,6-dimethylpyrimidine, 4-hydroxymethylpyrimidine, 3-hydroxy-6-methylpyridine, 4-benzylpyridine, 5-methylpyrimidine, 2,4-dimethoxypyrimidine, 2,4,6-trimethoxypyrimidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 1,5-diazabicyclo[4.3.0]-5-nonene.

[0031] According to certain preferred embodiments of the present invention, the molar ratio of the aliphatic diamine to the maleate is 1:2.

[0032] According to certain preferred embodiments of the present invention, the molar ratio of the 3-aminopropyltriethoxysilane to the polyaspartic acid ester is 4:1 to 4.2:1, preferably within the range of 4:1 to 4.05:1. If the molar ratio of the 3-aminopropyltriethoxysilane to the polyaspartic acid ester is less than 4:1, it will not be possible to ensure that both ends of the polyaspartic acid ester are completely capped with silane. If the molar ratio of the 3-aminopropyltriethoxysilane to the polyaspartic acid ester is greater than 4.2:1, the presence of excessive 3-aminopropyltriethoxysilane in the reaction system may affect the physical properties of the product.

[0033] According to certain preferred embodiments of the present invention, the ratio of the weight of the catalyst to the sum of the weights of the polyaspartic acid ester and 3-aminopropyltriethoxysilane is 5×10 -4 : 1 to 1×10 -3 : 1. Preferably within the range of 1×10 -4 : 1 to 5×10 -3 : 1.

[0034] Specifically, the preparation method of the silane-terminated polyaspartic acid ester comprises the following steps: (1) slowly adding maleate to aliphatic diamine under nitrogen protection, stirring and heating to 80-90° C. for 18-24 hours to react to obtain polyaspartic acid ester; (2) Adding 3-aminopropyltriethoxysilane and a catalyst to the polyaspartic acid ester obtained in step (1), stirring and mixing, reacting at a temperature of 70-120° C. and a pressure of -0.085-0.095 MPa for 2-5 hours, and simultaneously performing reduced pressure distillation to remove the generated by-products, to obtain the silane-terminated polyaspartic acid ester.

[0035] According to another aspect of the present invention, a silane-terminated polyaspartic acid ester is provided as a primer for preparing a highly weather-resistant base-and-surface anti-corrosion coating.

[0036] The highly weather-resistant bottom-to-top anti-corrosion coating consists of component A and component B: Component A: 50-80 parts by weight of the silane-terminated polyaspartic acid ester according to claim 1, 10-30 parts by weight of rutile titanium dioxide, 0.5-1.5 parts by weight of a dispersant, 0.5-0.8 parts by weight of a defoamer, 0.1-0.3 parts by weight of a leveling agent, 1-4 parts by weight of a chemical dewatering agent, 0.3-0.6 parts by weight of a UV absorber and 2-20 parts by weight of a solvent.

[0037] Component B: 10-15 parts by weight of HDI trimer, 50-75 parts by weight of polyisocyanate elastic curing agent, and 10-20 parts by weight of solvent.

[0038] The component A and the component B are packaged in an isolated manner to obtain the highly weather-resistant bottom-and-top integrated anti-corrosion coating.

[0039] According to certain embodiments of the present invention, the titanium dioxide is rutile titanium dioxide, for example, one or more of rutile titanium dioxide R902 and R105 provided by DuPont can be used. The dispersant is an anionic wetting and dispersing agent, for example, one or more of RHEOBYK 110 and RHEOBYK 111 provided by BYK in Germany can be used. The leveling agent is one or more of an organosilicon leveling agent or a modified acrylic leveling agent, for example, one of RHEOBYK 410 and RHEOBYK 411 provided by BYK in Germany can be used. The defoamer is a polyolefin solution defoamer, for example, one or more of BYK-1790 and BYK-1799 provided by BYK in Germany can be used. The ultraviolet absorber is one or more of benzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, benzotriazole ultraviolet absorbers, substituted acrylonitrile ultraviolet absorbers, and triazine ultraviolet absorbers. For example, one or more of RIASORB UV-326, RIASORB UV-928, and RIASORB UV-360 produced by Tianjin Lianlong Company can be used. The chemical dehydrating agent is a vinyl silane chemical dehydrating agent, such as A171 produced by Nanjing Aocheng Chemical. The solvent is selected from one or more of butyl acetate, diethyl carbonate, propylene glycol methyl ether acetate, and xylene. The HDI trimer is Desmodur from Covestro, Germany. ® N3390 or Duranate from Asahi Kasei ® The polyisocyanate elastic curing agent is one of polyether isocyanate prepolymer and polyester isocyanate prepolymer, such as Desmodur from Covestro, Germany. ® N3800 or Duranate from Asahi Kasei ® One or more of 4402-90T.

[0040] The present invention will be described in more detail below with reference to the examples. It should be noted that these descriptions and examples are intended to facilitate understanding of the present invention and are not intended to limit the present invention. The scope of protection of the present invention shall be subject to the appended claims.

[0041] In the present invention, unless otherwise noted, the reagents employed are commercial products and are used directly without further purification. In addition, the "%" mentioned is "% by weight" and the "parts" mentioned are "parts by weight".

[0042] Test Method In the following examples, the physical properties and anti-corrosion performance of each anti-corrosion coating obtained in each example were measured and the measurement results are listed in Table 1. The specific measurement methods are as follows: Substrate adhesion test Testing is conducted according to the relevant test methods in GB / T 5210-2006, "Adhesion Test for Paints and Clear Coatings by Pull-Off Method." If the adhesion is greater than or equal to 4 MPa, it is considered to meet the general industrial application requirements for anti-corrosion coating materials for steel structures used in construction. If the adhesion is greater than or equal to 7 MPa, the adhesion performance of the anti-corrosion coating material for steel structures used in construction is considered to be excellent.

[0043] Acid resistance Tests are conducted according to the relevant test methods in GB / T 9274-1988, "Determination of Resistance of Paints and Varnishes to Liquid Media." If the acid resistance is greater than or equal to 96 hours, it is considered to meet the general industrial application requirements of anti-corrosion coating materials for building steel structures. If the acid resistance is greater than or equal to 168 hours, the anti-corrosion coating for building steel structures is considered to have excellent acid resistance.

[0044] Salt water resistance Tests are conducted according to the relevant test methods in GB / T9274-1988, "Determination of Resistance of Paints and Varnishes to Liquid Media." If the salt water resistance is greater than or equal to 120 hours, it is considered to meet the general industrial application requirements of anti-corrosion coating materials for building steel structures. If the salt water resistance is greater than or equal to 240 hours, the anti-corrosion coating for building steel structures is considered to have excellent salt water resistance.

[0045] Salt spray resistance Testing is conducted according to the relevant test methods in GB / T 1771-2007, "Paints and varnishes - Determination of resistance to neutral salt spray." If the salt spray resistance is greater than or equal to 500 hours, it is considered to meet the general industrial application requirements of anti-corrosion coating materials for building steel structures. If the salt spray resistance is greater than or equal to 1000 hours, the anti-corrosion coating for building steel structures is considered to have excellent salt spray resistance.

[0046] Resistance to artificial aging Testing is conducted according to the relevant test methods in GB / T 1865-2009, "Paints and varnishes - Artificial Weathering and Artificial Radiation Exposure." If the artificial weathering resistance is greater than or equal to 500 hours, it is considered to meet the general industrial application requirements for anti-corrosion coating materials for building steel structures. If the artificial weathering resistance is greater than or equal to 1000 hours, the anti-corrosion coating for building steel structures is considered to have excellent artificial weathering resistance.

[0047] wear resistance Testing is conducted according to the relevant test methods in GB / T 1768-2006, "Paints and varnishes - Determination of abrasion resistance - Rotating rubber wheel method." If the abrasion resistance is 40 mg / 1000 revolutions or less, the coating is considered to meet the general industrial application requirements for anti-corrosion coatings for steel structures used in construction. If the abrasion resistance is 15 mg / 1000 revolutions or less, the coating is considered to have excellent wear resistance. Example 1

[0048] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet, and a gas escape tube, 40 g of 4,4'-diaminodicyclohexylmethane (Shandong Wanhua Chemical) was added, nitrogen was introduced, and 65.5 g of diethyl maleate (Shanghai Aladdin Company) was slowly added thereto. The mixture was heated to 80°C and reacted for 18 h to obtain polyaspartic acid ester L1.

[0049] In a three-necked flask equipped with a stirring rod, a thermometer, and a collecting device, 160 g of 3-aminopropyltriethoxysilane (Shanghai Aladdin Company) and 0.05 g of catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene were added to 100 g of polyaspartic acid ester L1 and mixed evenly. The mixture was reacted at -0.095 MPa and 75°C for 3 h, and the ethanol produced by the reaction was removed by reduced pressure distillation to obtain silane-terminated polyaspartic acid ester S1.

[0050] 58 g of dried rutile titanium dioxide (DuPont R902), 1.1 g of dispersant (RHEOBYK-110) and 10 g of butyl acetate were added to 200 g of silane-terminated polyaspartic acid ester S1, and the mixture was dispersed at a speed of 1000 r / min for 1 h; then 0.1 g of defoamer (BYK-1790), 0.1 g of leveling agent (RHEOBYK-410), 0.2 g of ultraviolet absorber (RIASORB UV-360) and 1.5 g of chemical dewatering agent (A171) were added in sequence, and after uniform dispersion, the highly weather-resistant bottom-to-top integrated anti-corrosion coating component A was obtained. 20 g of HDI trimer (Desmodur® N3390 from Covestro, Germany), 100 g of polyisocyanate elastic curing agent (Desmodur® N3800 from Covestro, Germany) and 15 g of butyl acetate were mixed and stirred uniformly to obtain the highly weather-resistant bottom-to-top anti-corrosion coating component B.

[0051] When in use, component A and component B are mixed in a ratio of 2:1 to obtain the highly weather-resistant bottom-to-top anti-corrosion coating. Example 2

[0052] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 560 g of 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane (BASF, Germany) was added, nitrogen was introduced, and 1072.82 g of diethyl maleate (Shanghai Aladdin Company) was slowly added thereto. The mixture was heated to 85°C and reacted for 36 h to obtain polyaspartic acid ester L2.

[0053] In a three-necked flask equipped with a stirring rod, a thermometer and a collecting device, 510 g of 3-aminopropyltriethoxysilane (Shanghai Aladdin Company) and 0.72 g of catalyst 1,5-diazabicyclo[4.3.0]-5-nonene were added to 400 g of polyaspartic acid ester L2 and mixed evenly. The mixture was reacted at -0.095 MPa and 110°C for 4 h, and the n-butanol produced by the reaction was removed by reduced pressure distillation to obtain silane-terminated polyaspartic acid ester S2.

[0054] 370 g of dried rutile titanium dioxide (DuPont R105), 14 g of dispersant (RHEOBYK-111) and 240 g of diethyl carbonate were added to 800 g of silane-terminated polyaspartic acid ester, and the mixture was dispersed at a speed of 1500 r / min for 1.5 h; then 1 g of defoamer (BYK-1799), 1.5 g of leveling agent (RHEOBYK-411), 15 g of ultraviolet absorber (RIASORB UV-928) and 66 g of chemical dewatering agent (A171) were added in sequence, and after uniform dispersion, the highly weather-resistant bottom-to-top anti-corrosion coating component A was obtained. 150 g of HDI trimer (Desmodur® N3390 from Covestro, Germany), 500 g of polyisocyanate elastic curing agent (Desmodur® N3800 from Covestro, Germany) and 180 g of diethyl carbonate were mixed and stirred uniformly to obtain the highly weather-resistant bottom-to-top anti-corrosion coating component B.

[0055] When in use, component A and component B are mixed in a ratio of 2.5:1 to obtain the highly weather-resistant bottom-to-top anti-corrosion coating. Example 3

[0056] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 90 g of 1,6-hexanediamine (Shanghai Aladdin Company) was added, nitrogen was introduced, and 266.72 g of diethyl maleate (Shanghai Aladdin Company) was slowly added thereto. The mixture was heated to 75°C and reacted for 18 h to obtain polyaspartic acid ester L3.

[0057] In a three-necked flask equipped with a stirring rod, a thermometer and a collecting device, 675 g of 3-aminopropyltriethoxysilane (Shanghai Aladdin Company) and 1 g of catalyst 5-methylpyrimidine were added to 350 g of polyaspartic acid ester L3 and mixed evenly. The mixture was reacted at -0.090 MPa and 80°C for 2 h, and the ethanol produced by the reaction was removed by reduced pressure distillation to obtain silane-terminated polyaspartic acid ester S3.

[0058] 195g of dried rutile titanium dioxide (DuPont R105), 6.8g of dispersant (RHEOBYK-110) and 90g of propylene glycol methyl ether acetate were added to 360g of silane-terminated polyaspartic acid ester and dispersed at a speed of 1200r / min for 1h; 0.5g of defoamer (BYK-1790), 0.8g of leveling agent (RHEOBYK-411), 9g of ultraviolet absorber (RIASORB UV-360) and 20g of chemical dewatering agent (A171) were then added in sequence and dispersed evenly to obtain the high weather resistance bottom and surface integrated anti-corrosion coating component A. 100g of HDI trimer (Duranate ® TPA-100), 300 g of polyisocyanate elastic curing agent (Desmodur® N3800 from Covestro, Germany) and 150 g of propylene glycol methyl ether acetate were mixed and stirred evenly to obtain the high weather-resistant bottom-to-top anti-corrosion coating component B.

[0059] When in use, component A and component B are mixed in a ratio of 2.1:1 to obtain the highly weather-resistant bottom-to-top anti-corrosion coating. Example 4

[0060] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 144 g of 1,8-octanediamine (Shanghai Aladdin Company) was added, nitrogen was introduced, and 288 g of dimethyl maleate (Shanghai Aladdin Company) was slowly added thereto. The mixture was heated to 75°C and reacted for 20 h to obtain polyaspartic acid ester L4.

[0061] In a three-necked flask equipped with a stirring rod, a thermometer and a collecting device, 420 g of 3-aminopropyltriethoxysilane (Shanghai Aladdin Company) and 0.09 g of catalyst 2,4-dimethoxypyrimidine were added to 200 g of polyaspartic acid ester L4 and mixed evenly. The mixture was reacted at -0.095 MPa and 70°C for 2 h while being distilled under reduced pressure to remove the methanol produced by the reaction, thereby obtaining silane-terminated polyaspartic acid ester S4.

[0062] 94g of dried rutile titanium dioxide (R902 from DuPont, USA), 2g of dispersant (RHEOBYK-110) and 50g of xylene were added to 450g of silane-terminated polyaspartic acid ester and dispersed at a speed of 1000r / min for 2h; 0.05g of defoamer (BYK-1799), 0.15g of leveling agent (RHEOBYK-410), 2g of UV absorber (RIASORBUV-326) and 6.6g of chemical dewatering agent (A171) were then added in sequence and dispersed evenly to obtain the high weather resistance bottom and surface all-in-one anti-corrosion coating component A. 80g of HDI trimer (Duranate ® TPA-100), 160g polyisocyanate elastic curing agent (Duranate ® 4402-90T) and 90 g of xylene were mixed and stirred evenly to obtain the high weather resistance bottom and surface all-in-one anti-corrosion coating component B.

[0063] When in use, component A and component B are mixed in a ratio of 2:1 to obtain the highly weather-resistant bottom-to-top anti-corrosion coating. Example 5

[0064] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet, and a gas escape tube, 170 g of isophorone diamine (BASF, Germany) was added, nitrogen was introduced, and 365 g of diethyl maleate (Aladdin, Shanghai) was slowly added thereto. The mixture was heated to 80°C and reacted for 22 h to obtain polyaspartic acid ester L5.

[0065] In a three-necked flask equipped with a stirring rod, a thermometer and a collecting device, 180 g of 3-aminopropyltriethoxysilane (Shanghai Aladdin Company) and 0.05 g of catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene were added to 100 g of polyaspartic acid ester L5 and mixed evenly. The mixture was reacted at -0.095 MPa and 70°C for 2 h, and the ethanol produced by the reaction was removed by reduced pressure distillation to obtain silane-terminated polyaspartic acid ester S5.

[0066] 70g of dried rutile titanium dioxide (DuPont R105), 0.5g of dispersant (RHEOBYK-111) and 10g of butyl acetate were added to 150g of silane-terminated polyaspartic acid ester and dispersed at a speed of 1000r / min for 1h; 0.08g of defoamer (BYK-1799), 0.15g of leveling agent (RHEOBYK-411), 0.2g of UV absorber (RIASORB UV-928) and 2g of chemical dewatering agent (A171) were then added in sequence and dispersed evenly to obtain the high weather resistance bottom and surface all-in-one anti-corrosion coating component A. 50g of HDI trimer (Duranate ®TPA-100), 80g polyisocyanate elastic curing agent (Duranate ® 4402-90T) and 25 g of xylene were mixed and stirred evenly to obtain the high weather resistance bottom and surface all-in-one anti-corrosion coating component B.

[0067] When in use, component A and component B are mixed in a ratio of 1.5:1 to obtain the highly weather-resistant bottom-to-top anti-corrosion coating. Example 6

[0068] In a four-necked flask equipped with a stirring rod, thermometer, nitrogen inlet and gas escape tube, 900 g of 4,4'-diaminodicyclohexylmethane (BASF, Germany) was added, nitrogen was introduced, and 1953.33 g of dibutyl maleate (Aladdin, Shanghai) was slowly added thereto. The mixture was heated to 90°C and reacted for 35 h to obtain polyaspartic acid ester L6.

[0069] In a three-necked flask equipped with a stirring rod, a thermometer and a collecting device, 2700 g of 3-aminopropyltriethoxysilane (Shanghai Aladdin Company) and 2.45 g of catalyst 1,5-diazabicyclo[4.3.0]-5-nonene were added to 2000 g of polyaspartic acid ester L6 and mixed evenly. The mixture was reacted at -0.095 MPa and 120°C for 3 h, and the butanol produced by the reaction was removed by reduced pressure distillation to obtain silane-terminated polyaspartic acid ester S6.

[0070] 1500g of dried rutile titanium dioxide (R902 from DuPont, USA), 50g of dispersant (RHEOBYK-110) and 300g of propylene glycol methyl ether acetate were added to 3500g of silane-terminated polyaspartic acid ester and dispersed at a speed of 1500r / min for 2h; then 7.8g of defoamer (BYK-1790), 13.4g of leveling agent (RHEOBYK-411), 28g of UV absorber (RIASORB UV-928) and 70g of chemical dewatering agent (A171) were added in sequence and dispersed evenly to obtain the high weather resistance bottom and surface integrated anti-corrosion coating component A. 1000g of HDI trimer (Duranate ® TPA-100), 2200g polyisocyanate elastic curing agent (Duranate ® 4402-90T) and 800 g of xylene were mixed and stirred evenly to obtain the high weather resistance bottom and surface all-in-one anti-corrosion coating component B.

[0071] When in use, component A and component B are mixed in a ratio of 2:1 to obtain the highly weather-resistant bottom-to-top anti-corrosion coating. Comparative Example 1

[0072] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet, and a gas escape tube, 40 g of 4,4'-diaminodicyclohexylmethane (Shandong Wanhua Chemical) was added, nitrogen was introduced, and 65.5 g of diethyl maleate (Shanghai Aladdin Company) was slowly added thereto. The mixture was heated to 80°C and reacted for 18 h to obtain polyaspartic acid ester D1.

[0073] 58 grams of dried rutile titanium dioxide (DuPont R902), 1.1 grams of dispersant (RHEOBYK-110) and 10 grams of butyl acetate were added to 200 grams of polyaspartic acid ester D1, and the mixture was dispersed at a high speed of 1000 r / min for 1 hour; then 0.1 grams of defoamer (BYK-1790), 0.1 grams of leveling agent (RHEOBYK-410), 0.2 grams of ultraviolet absorber (RIASORB UV-360) and 1.5 grams of chemical dewatering agent (A171) were added in sequence, and after uniform dispersion, the highly weather-resistant bottom-to-top integrated anti-corrosion coating component A was obtained. 20 g of HDI trimer (Desmodur® N3390 from Covestro, Germany), 100 g of polyisocyanate elastic curing agent (Desmodur® N3800 from Covestro, Germany) and 15 g of butyl acetate were mixed and stirred uniformly to obtain the highly weather-resistant bottom-to-top anti-corrosion coating component B.

[0074] When in use, component A and component B are mixed in a ratio of 2.2:1 to obtain the highly weather-resistant bottom-to-top anti-corrosion coating. Comparative Example 2

[0075] In a four-necked flask equipped with a stirring rod, a thermometer, a nitrogen inlet and a gas escape tube, 560 g of 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane (BASF, Germany) was added, nitrogen was introduced, and 1072.82 g of diethyl maleate (Shanghai Aladdin Company) was slowly added thereto. The mixture was heated to 85°C and reacted for 36 h to obtain polyaspartic acid ester D2.

[0076] 370 g of dried rutile titanium dioxide (DuPont R105), 14 g of dispersant (RHEOBYK-111) and 240 g of diethyl carbonate were added to 800 g of polyaspartic acid ester D2, and the mixture was dispersed at a speed of 1500 r / min for 1.5 h; then 1 g of defoamer (BYK-1799), 1.5 g of leveling agent (RHEOBYK-411), 15 g of ultraviolet absorber (RIASORB UV-928) and 66 g of chemical dewatering agent (A171) were added in sequence, and after uniform dispersion, the highly weather-resistant bottom-to-top integrated anti-corrosion coating component A was obtained. 150 g of HDI trimer (Desmodur® N3390 from Covestro, Germany), 500 g of polyisocyanate elastic curing agent (Desmodur® N3800 from Covestro, Germany) and 180 g of diethyl carbonate were mixed and stirred uniformly to obtain the highly weather-resistant bottom-to-top anti-corrosion coating component B.

[0077] When in use, component A and component B are mixed in a ratio of 2.8:1 to obtain the highly weather-resistant bottom-to-top anti-corrosion coating.

[0078] Table 1 Performance test results of the anticorrosive coatings obtained in Examples 1-6 and Comparative Examples 1-2

[0079] Examples 1-6 above demonstrate that when silane-terminated polyaspartic acid esters prepared by the method of the present invention are applied to anti-corrosion coatings, the resulting anti-corrosion coatings can achieve excellent anti-corrosion effects. In particular, Examples 1-6 demonstrate that when highly weather-resistant, bottom-to-top anti-corrosion coatings are prepared according to the technical solution of the present invention, the resulting anti-corrosion coatings exhibit excellent adhesion to the substrate, and the resulting cured products exhibit excellent anti-corrosion and anti-aging properties, achieving excellent levels of wear resistance.

[0080] Comparing the results of Comparative Examples 1 and 2 in Table 1 shows that when uncapped polyaspartic acid ester is used as a raw material to prepare an anti-corrosion coating, its anti-corrosion performance and aging resistance can reach good levels, but its adhesion to the substrate does not reach the "excellent" level. After silane capping (Examples 1 and 2), the substrate adhesion and wear resistance of the substrate prepared using this raw material are significantly improved.

[0081] The embodiments described in the present invention are merely descriptions of the preferred implementation methods of the present invention and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should fall within the scope of protection of the present invention. The technical contents for which protection is sought in the present invention have all been recorded in the claims.

Claims

1. A silane-terminated polyaspartic acid ester, characterized in that: The silane-terminated polyaspartic acid ester has a structure represented by the following general formula (1): ; General formula (1) Where R is C2-C 15 A divalent aliphatic group.

2. The method for preparing the silane-terminated polyaspartic acid ester according to claim 1, wherein The preparation method comprises the following steps: (1) slowly adding maleate to aliphatic diamine under nitrogen protection, stirring and heating to react, thereby obtaining polyaspartic acid ester; (2) adding 3-aminopropyltriethoxysilane and a catalyst to the polyaspartic acid ester obtained in step (1), mixing and heating while performing reduced pressure distillation to remove the generated by-products, thereby obtaining the silane-terminated polyaspartic acid ester.

3. The preparation method of silane-terminated polyaspartic acid ester according to claim 2, characterized in that, The aliphatic diamine is selected from one or more of ethylenediamine, 1,4-butanediamine, 1,6-hexanediamine, 1,4-cyclohexanediamine, 1,8-octanediamine, 1,10-decanediamine, isophoronediamine, 4,4'-diaminodicyclohexylmethane, and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane; the maleate is selected from one or more of dimethyl maleate, diethyl maleate, and dibutyl maleate; and the catalyst is selected from one or more of pyrrole compounds, pyridine compounds, imidazole compounds, and pyrimidine compounds.

4. The method for preparing silane-terminated polyaspartic acid ester according to claim 3, wherein The catalyst is selected from one or more of 2,3-dihydroxypyridine, 4,6-dimethylpyrimidine, 4-hydroxymethylpyrimidine, 3-hydroxy-6-methylpyridine, 4-benzylpyridine, 5-methylpyrimidine, 2,4-dimethoxypyrimidine, 2,4,6-trimethoxypyrimidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 1,5-diazabicyclo[4.3.0]-5-nonene.

5. The method for preparing silane-terminated polyaspartic acid ester according to claim 2, wherein The molar ratio of the aliphatic diamine to the maleate is 1:

2.

6. The method for preparing silane-terminated polyaspartic acid ester according to claim 2, wherein The molar ratio of the 3-aminopropyltriethoxysilane to the polyaspartic acid ester is 4:1 to 4.2:

1.

7. The method for preparing silane-terminated polyaspartic acid ester according to claim 2, wherein The ratio of the weight of the catalyst to the sum of the weights of the polyaspartic acid ester and 3-aminopropyltriethoxysilane is 5×10 -4 :1 to 1×10 -3 :

1.

8. The use of the silane-terminated polyaspartic acid ester according to claim 1, characterized in that: Used to prepare highly weather-resistant base-to-surface anti-corrosion coatings.

9. A highly weather-resistant bottom-to-top anti-corrosion coating, characterized in that: The anti-corrosion coating consists of component A and component B, wherein: Component A: 50-80 parts by weight of the silane-terminated polyaspartic acid ester according to claim 1, 10-30 parts by weight of rutile titanium dioxide, 0.5-1.5 parts by weight of a dispersant, 0.5-0.8 parts by weight of a defoamer, 0.1-0.3 parts by weight of a leveling agent, 1-4 parts by weight of a chemical dehydrating agent, 0.3-0.6 parts by weight of a UV absorber, and 2-20 parts by weight of a solvent; Component B: 10-15 parts by weight of HDI trimer, 50-75 parts by weight of polyisocyanate elastic curing agent, and 10-20 parts by weight of solvent; The component A and the component B are packaged in an isolated manner to obtain the highly weather-resistant bottom-and-top integrated anti-corrosion coating.

10. The highly weather-resistant bottom-and-top integrated anti-corrosion coating according to claim 9, characterized in that: The dispersant is an anionic wetting and dispersing agent; and / or The defoamer is a polyolefin solution type defoamer; and / or The leveling agent is one or more of an organosilicon leveling agent and a modified acrylic leveling agent; and / or The chemical dewatering agent is a vinylsilane chemical dewatering agent; and / or The ultraviolet absorber is one or more of a benzophenone ultraviolet absorber, a salicylate ultraviolet absorber, a benzotriazole ultraviolet absorber, a substituted acrylonitrile ultraviolet absorber and a triazine ultraviolet absorber; and / or The solvent is selected from one or more of butyl acetate, diethyl carbonate, propylene glycol methyl ether acetate and xylene.